Collaborative Governance dalam Pengembangan Desa Wisata Berkelanjutan: Program Bakti BCA sebagai Acuan Akselerasi Pariwisata Desa di Kabupaten Tuban - Aura Alviani Zahra; Nihayatus Sholichah; Dandy Patria W; Ika Devy Pramudiana (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Sustainable tourism village development requires effective multi-party collaboration between government, private sector, and communities. This study aims to analyze the implementation of Collaborative Governance in the Bakti BCA Program as a reference for accelerating village tourism in Tuban Regency. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and document analysis at four assisted locations namely Bektiharjo Tourism Village, Kelapa Beach, Geger Tourism Village, and Sowan Beach. The results showed that the Bakti BCA Program has successfully implemented Collaborative Governance principles through inclusive multi-stakeholder involvement, formal and structured collaboration processes, consensus-based decision making, and shared value creation. The program had a significant positive impact with a 428% increase in total tourist visits, 559% growth in MSMEs, and 156% increase in community income during the 2021-2024 period. The collaboration between PT Bank Central Asia Tbk, Tuban Regency Government, and local communities can serve as a reference model for sustainable tourism village development in other regions with strengthening self-reliance strategies for long-term sustainability.